1988
DOI: 10.1159/000217569
|View full text |Cite
|
Sign up to set email alerts
|

Trophoblast-Specific &beta;<sub>1</sub>-Glycoprotein: Its Spatial Structure and Localization of Antigenic Determinants

Abstract: Effects of temperature and pH on the spatial structures of trophoblast-specific β1 -glycoprotein (TSG) and its various derivatives and fragments have been studied by circular dichroic spectroscopy. The spatial organization of the protein portion of TSG derivatives, as revealed by the spectroscopic evidence, has been discussed with respect to the antigenic activity of the species studied. We concluded that the TSG protein portion consists mainly of a β-structural type. The antigenic determinants were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Although the holothurian MBL- AJ and mammalian lectins, including human MBL, had common properties to recognize bacterial mannans, the differences in the carbohydrate-binding specificities were found to be significant [5] . It has been previously shown that holothurian lectin MBL- AJ interacts with the promising cancer biomarkers in the following order of the lectin-binding affinity: CEA, embryonic α-1-acid glycoprotein, trophoblast-specific β1-glycoprotein and α-fetoprotein isolated from the abortive and retroplacental blood [13] , [30] , [31] , [32] . MBL- AJ is not inhibited by monosaccharide, which is in the content of the normal human glycoconjugate's carbohydrate chains, and does not interact with the human blood serum components.…”
Section: Discussionmentioning
confidence: 99%
“…Although the holothurian MBL- AJ and mammalian lectins, including human MBL, had common properties to recognize bacterial mannans, the differences in the carbohydrate-binding specificities were found to be significant [5] . It has been previously shown that holothurian lectin MBL- AJ interacts with the promising cancer biomarkers in the following order of the lectin-binding affinity: CEA, embryonic α-1-acid glycoprotein, trophoblast-specific β1-glycoprotein and α-fetoprotein isolated from the abortive and retroplacental blood [13] , [30] , [31] , [32] . MBL- AJ is not inhibited by monosaccharide, which is in the content of the normal human glycoconjugate's carbohydrate chains, and does not interact with the human blood serum components.…”
Section: Discussionmentioning
confidence: 99%
“…Immunochemical analysis and SDS electrophore sis were carried out as described earlier [6,7], CD and CR spectra were recorded and analyzed as described earlier [7,8], Differential UV spectra of thermal per turbation were performed as reported earlier [7,9]. Polyclonal rabbit antisera were used in all the immu nochemical assays.…”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal rabbit antisera were used in all the immu nochemical assays. Antigenic activity was determined by the usual immune enzyme 'sandwich' assay as described earlier [7,10], using a borate buffer [11].…”
Section: Methodsmentioning
confidence: 99%